Simulation investigation of safety limits of helicopter operations - Stanis?awski, J. (My University, 2019)
The paper presents results of simulations concerning some aspects of helicopter operation safety which include the H-V zone limits, loss of tail rotor aerodynamic effectiveness, operations of ship-borne helicopter and maneuver flight. For simulation investigation, two kinds of physical models of helicopter with different simplification level of real rotorcraft structure are applied. For analysis of emergency situation after power loss, the helicopter is treated as point mass of fuselage suspended beneath main rotor in form of non-deformable disk area. To define the rotor loads and blade deflections generated in boundary flight states a more precise model of elastic blades is applied which consists of deformable blade axes with sets of lumped masses distributed along blade radius. The axis model allows flap, lead-lag and pitch motion of blade. Equations of motion of rotor blades are solved applying Runge-Kutta method. Data of light helicopter were applied for simulations. The simulation investigation may help to collect data for prediction conditions of helicopter flight which can generate potentially dangerous situations.